Efektifitas Pembayaran Iuran BPJS Kesehatan Dengan Sistem 1 Virtual Account (VA) Keluarga - Noor Anida Maysharoh; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2018)
This study was conducted aimed at describing and analyzing the effectiveness of BPJS Health contribution payments with the 1 Virtual Account (VA) Family system and to find out the factors that influence BPJS Health contribution payments with the 1 Virtual Account (VA) Family system. The method used in this study is a qualitative method with data collection carried out by observing, documenting, and interviewing informants and using sources of books, journals, and documents related to BPJS Kesehatan. The results of this study are that the payment of contributions made by a family 1 VA system is quite effective because with this system payments are made easier and faster, besides that the participants save more on administrative costs, besides being able to increase the flexibility of contributions because participants pay their contributions collectively in 1 household. In addition, there are factors that influence payment of BPJS Health contributions with the 1 Virtual Account (VA) Family system, namely the lack of knowledge of participants, lack of community participation, low income, considerable expenditure each month, motivation and distance.